2017
DOI: 10.1049/iet-cta.2016.1409
|View full text |Cite
|
Sign up to set email alerts
|

Control design for interval type‐2 polynomial fuzzy‐model‐based systems with time‐varying delay

Abstract: Citing this paper Please note that where the full-text provided on King's Research Portal is the Author Accepted Manuscript or Post-Print version this may differ from the final Published version. If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Remark 6: The research ideas of (38) and (39) of this study are firstly proposed in [23], which can alleviate the conservativeness of the system by introducing some slack matrices under the imperfect premise matching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 6: The research ideas of (38) and (39) of this study are firstly proposed in [23], which can alleviate the conservativeness of the system by introducing some slack matrices under the imperfect premise matching.…”
Section: Resultsmentioning
confidence: 99%
“…The common methods include Park's inequality [30], Jensen inequality [31], Wirtinger-based inequality [32], auxiliary function-based integral inequality [33], Bessel-Legendre inequality [34], generalised integral inequality [35], delay partitioning technique [36] etc. According to [35], we know that Jensen inequality, Wirtinger-based inequality, auxiliary function-based integral inequality, Bessel-Legendre inequality can be regarded as special cases of generalised integral inequality with k = 0 and different values of l. The study of time-delay systems has gone deep into various types of systems, such as normal time-delay system [30][31][32][33][34][35]37], T-S fuzzy systems [38], T-S fuzzy singular systems [13,14,16,19,20,36], IT2 fuzzy systems [39,40]. The delay partitioning technique was adopted to handle the delay term in [36].…”
Section: Introductionmentioning
confidence: 99%
“…Remark 6. From the research point of view, the partially and imperfectly matched premises address the fundamental issues of some emerging research topics of FMB/PFMB control systems, such as time-delayed [104], sampleddata [140,68,71], observer-based [141,65], IT2 [105,106], networked [142,143,144] fuzzy control systems. For all these control systems, the grade of membership functions are not the same as those of the fuzzy model due to the system states obtained by the fuzzy controller are altered, say, by the time delay, sampling process, or observer.…”
Section: Imperfectly Matched Premisesmentioning
confidence: 99%
“…Since then, MFD stability analysis results using various membership function information and techniques can be found for the FMB control systems [91,92,93,75,94,95,96,97,98] and the PFMB control systems [76,77,79,82,85]. The MFI stability analysis has also extended to interval type-2 (IT2) FMB/PFMB control systems [99,100,101,102,103,104,105,106]. Further details regarding MFD stability analysis will be provided in the later sections.…”
Section: Introductionmentioning
confidence: 99%
“…To define nonlinear input-output mappings, it has been shown that Fuzzy Logic Systems (FLSs), especially Interval T2 (IT2) FLSs, are very powerful tools [13][14][15][16][17][18][19][20][21]. This lies due to the fact that IT2-FLSs use and employ IT2 Fuzzy Sets (FSs) that have more extra degree of freedom provided by the Footprint of Uncertainty (FOU) [13][14][15][16][17][18][19][20][21]. Hence, many theoretical studies have been presented on how the size/shape of the FOU affects the IT2 Fuzzy Mappings (FMs) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%